# -2+7x-{5x-[4y-(3-8x)+9]-10y}???solution po plss??

2
by Sheryllreyes817

2015-09-15T19:57:38+08:00

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
-2 + 7x - { 5x - [ 4y - (3 - 8x ) + 9 ] - 10y }
-2 7x + -5x - 4y - 3 - 8x + 9 ) -10y )
-2 + 7x + -1 ( 5x) + - 1 ( -4y ) + ( -1 ) ( 3 ) + -1 ( -8x ) + ( -1 ) ( -9 ) + - 1 ( -10y )
-2 + 7x + - 5x + 4y + -3 + 8x + 9+10y
7x + -5x 8x 4y 10y ( -+ -+9 )
10x 14y 4
-KookEin
• Brainly User
2015-09-15T20:13:49+08:00

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
PEMDAS and Rule on subtraction of polynomials, where the signs of each term of the subtrahend is changed, then proceed to addition rule.

1.)Simplify the inner part:
4y-(3-8x)+9
= 4y + (-3 + 8x) + 9
= 4y - 3 + 9 + 8x
= 4y + 8x + 6

2)  5x - (4y + 8x + 6)-10y
= 5x + (-4y - 8x - 6) - 10y
= 5x - 4y - 8x - 6- 10y
= 5x - 8x - 4y- 10y - 6
= -3x -4y - 10y - 6
= -3x -14y -6

3) -2 + 7x - (-3x -14y -6)
= -2 + 7x + (+3x +14y + 6)
= -2 + 7x + 3x + 14y  + 6
= 7x + 3x + 14y + - 2 + 6
= 10x + 14y + 4

FINAL ANSWER: 10x + 14y + 4